1988
DOI: 10.1029/jc093ic05p05051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of El Nino‐Southern Oscillation and North Pacific weather patterns on interannual variability in the subarctic Bering Sea

Abstract: Extraordinary interannual variability in ice cover, air and sea surface temperatures (SST), and surface winds in the eastern Bering Sea have been observed over recent years. To investigate the causes of this interannual variability, long-term (20-30 years) time series of air, ocean, and ice parameters from the Bering Sea were cross-correlated with the southern oscillation index (SOI), an index of E1 Nino-Southern Oscillation (ENSO) events in the tropical southern hemisphere, as well as with an index of Pacific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 26 publications
5
76
2
Order By: Relevance
“…The NPO pattern, of course, exerts a strong influence over the Pacific basin; Di Lorenzo et al (2008) found that the NPO serves as the atmospheric forcing pattern for the oceanic NPGO pattern. Previous studies also emphasized that the regional Bering Sea variability is closely related to the state of the entire Pacific climate system (Niebauer 1988;Minobe 2002). Figure 10 displays the regressed spatial patterns of SSTA and 1,000-hPa geopotential height anomalies over the tropical and North Pacific (100°E-80°W, 10°S-70°N).…”
Section: Covariability Of Bering Sea Sst and Pacific Large-scale Circmentioning
confidence: 92%
See 2 more Smart Citations
“…The NPO pattern, of course, exerts a strong influence over the Pacific basin; Di Lorenzo et al (2008) found that the NPO serves as the atmospheric forcing pattern for the oceanic NPGO pattern. Previous studies also emphasized that the regional Bering Sea variability is closely related to the state of the entire Pacific climate system (Niebauer 1988;Minobe 2002). Figure 10 displays the regressed spatial patterns of SSTA and 1,000-hPa geopotential height anomalies over the tropical and North Pacific (100°E-80°W, 10°S-70°N).…”
Section: Covariability Of Bering Sea Sst and Pacific Large-scale Circmentioning
confidence: 92%
“…In particular, its relationship with climate variability has long been the focus of attention (Grebmeier et al 2006;Overland and Stabeno 2004;Hunt et al 2002;Kruse 1998;Brodeur et al 1999). Furthermore, the Bering Sea, as a marginal section of the North Pacific Ocean, is sensitive to Pacific largescale climate phenomena such as the El Niño/Southern Oscillation (ENSO) (Niebauer 1988) and the Pacific Decadal Oscillation (PDO) (Hare and Mantua 2000;Overland et al 1999). Understanding the oceanic and atmospheric variability over the Bering Sea, therefore, is essential from both ecological and climatological perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For sea ice, as well as for other environmental variables such as temperatures, winds, etc. [e.g., Niebauer, 1988], most of the interannual variability in the Bering Sea region is driven by winter conditions when there is a minimum of insolation and a maximum in atmospheric advection. Interannual variability is typically not driven by summer In summer the Aleutian low is nearly nonexistent and the Bering Sea is between the northern portions of the North Pacific high and low pressure over Asia.…”
mentioning
confidence: 99%
“…The annual mean SST in the North Pacific Ocean for each year was recalculated and compared with the mean SST from 1975SST from -2004. The Southern Oscillation Index (SOI), which is the difference in sea level pressure between Tahiti and Darwin, is an effective indicator of El Niño events in the North Pacific Ocean (Niebauer 1988). The SOI data obtained from the National Oceanic and Atmospheric Administration Climate Prediction Center (NOAA/CPC) were also transformed into anomalies as SST.…”
Section: Data Sourcementioning
confidence: 99%